Cellulose Nata de Sago-Hyaluronic Acid Microneedle for Pneumococcal Conjugate Vaccine - Saranani, Selpirahmawati; Laugi, Putri S.; K., Intan N.A.; Lakapu, Sonia M.; Syian, Alfiyani; Jayanti, Seftika (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
The use of syringe-administered vaccines has significantly increased immunization coverage among children. Still, pneumonia remains the leading cause of death in children under five worldwide, accounting for over 70% of fatalities in this age group. To address challenges such as needle phobia, transdermal drug delivery systems offer a promising, minimally invasive alternative for both local and systemic medication administration. This study focuses on developing and evaluating a nata de sago-hyaluronic acid cellulose microneedle formulation for the transdermal delivery of pneumonia vaccines in children. The study consisted of preparing nata de sago, cellulose suspension, microneedle fabrication, and subsequent characterization and effectiveness testing. Results showed that the microneedle reached swelling equilibrium with a swelling degree of 1. Diffusion tests revealed a drug release rate of 1.173% within 90 minutes, successfully penetrating the stratum corneum. Scanning Electron Microscopy (SEM) analysis confirmed an average microneedle length of 763.6 μm and a width of 191.7 μm for Pin 12, demonstrating its suitability for transdermal application. These findings highlight the nata de sago-hyaluronic acid microneedle as a well-designed and effective platform for pneumococcal vaccine delivery, offering a novel solution to improve pediatric immunization and address key challenges in child healthcare.